2019
DOI: 10.1002/pds.4889
|View full text |Cite
|
Sign up to set email alerts
|

Data variability across Canadian administrative health databases: Differences in content, coding, and completeness

Abstract:  The Canadian Network for Observational Drug Effect Studies uses administrative databases across Canada to conduct drug safety and effectiveness studies. The populations and drugs covered by provincial programs, versions and precision of the International Classification of Diseases coding system in physician claims, and content and completeness of hospital discharge abstracts varies across provinces and over time. The heterogeneity amongst provincial databases can potentially introduce differences in study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Variation in the validation results are consistent with the results of a previous multi-database study conducted by CNODES that showed substantial variation across Canadian provinces in the association of medication exposure with health outcomes [ 26 ]; these variations were attributed to differences in the data, including diagnostic coding practices. While Canada has a universal healthcare system, the responsibility for delivery of services exists with the individual provinces and territories.…”
Section: Discussionsupporting
confidence: 83%
“…Variation in the validation results are consistent with the results of a previous multi-database study conducted by CNODES that showed substantial variation across Canadian provinces in the association of medication exposure with health outcomes [ 26 ]; these variations were attributed to differences in the data, including diagnostic coding practices. While Canada has a universal healthcare system, the responsibility for delivery of services exists with the individual provinces and territories.…”
Section: Discussionsupporting
confidence: 83%
“…10 These results may not be generalizable to the United States given the single payer healthcare system in Canada and heterogeneity of administrative data for individuals in a single province. 19 Sharoky et al studied practice patterns and post-operative outcomes for male vs. female surgeons in three states with strict inclusion criteria. The cohort was limited to Medical Doctors age 30-70 trained in the United States practicing General Surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In Quebec, all secondary diagnoses are captured on the hospital discharge summary, which could result in documentation of a higher prevalence of chronic conditions compared to other jurisdictions. 29 Due to these differences, for candidate variables that differed in prevalence in Quebec and other provinces, we examined their association with the main outcomes and created Quebec-specific covariates for variables with a higher prevalence but a lower risk of being an outcome. Finally, we compared the discriminative ability of our developed models against that of models used by the CIHI, using the Ontario data and the national data.…”
Section: Methodsmentioning
confidence: 99%